Synthesis and Characterization of a Carbon‐Supported Cobalt Nitride Nano‐Catalyst. Issue 2 (19th January 2022) - Rubab, Anosha; Baig, Nadeem; Sher, Muhammad; Ali, Mubarak; Ul‐Hamid, Anwar; Jabeen, Naila; Khan, Latif U.; Sohail, Manzar
Abstract: Transition metal nitrides have attracted great interest among the non‐noble catalysts employed in heterogeneous catalytic processes because of their exceptional stability and catalytic potential. However, the approach for their synthesis has remained a tremendous challenge. This study presents the synthesis of Co4 N/C catalyst fabricated at 400, 600, and 800 °, symbolized as Co4 N/C‐400, Co4 N/C‐600, Co4 N/C‐800, respectively. The characterization of fabricated catalysts is carried out through various advanced analytical techniques. As prepared nano‐catalyst Co4 N/C shows remarkable catalytic efficiency in terms of low activation energy ( Ea =3.038×10 −1  KJ mol −1 ), fast conversion rate ( Kapp =0.2884 s −1 ), and 97.57% conversion efficiency. Moreover, it also exhibits excellent stability and reusability because of its metallic characteristics. The outstanding catalytic activity of the catalyst is the combined effect in which the Co4 N nanoparticles acted as active sites, and the carbon support doped with nitrogen provided an expressway for the transport of electrons required for catalytic reduction. Moreover, the designed catalyst is immobilized on the cellulose membrane filter support, to demonstrate the catalytic reduction of 4‐nitrophenol to 4‐aminophenol. We envision that our work would facilitate the fabrication of cobalt nitrides‐based nano‐catalysts for a wide range of industrial applications. Abstract : A nano‐catalyst based on transition metal nitride has been synthesized and its catalytic activity towards selective hydrogenation reactions investigated. Moreover, the catalyst was immobilized on a cellulose membrane filter support, demonstrating the instantaneous catalytic reduction of 4‐nitrophenol to 4‐aminophenol.